Physicochemical, steric, and energetic characterization of kaolinite based silicate nano-sheets as potential adsorbents for safranin basic dye: effect of exfoliation reagent and techniques - Ali, Samar Mohamed; Mohamed, Reham A.; Abdel-Khalek, Ahmed A.; Ahmed, Ashour M.; Abukhadra, Mostafa (Frontiers in Chemistry, 2024)
Kaolinite was subjected to advanced exfoliation processes to form separated nano-silicate sheets (EXK) with enhanced physicochemical properties as adsorbents. This involved the incorporation of different exfoliating agents, urea (U/EXK), KNO3 (N/EXK), and CTAB (C/EXK), highlighting their impacts on their textural and surficial properties as adsorbents for safranin dye. The applied characterization techniques confirmed the higher exfoliating degree of C/EXK, followed by N/EXK and U/EXK. This appeared significantly in the determined surface area (55.7 m2/g (C/EXK), 36.7 m2/g (U/EXK), and 47.1 m2/g (N/EXK)) and adsorption performances. The C/EXK structure displayed a better safranin uptake capacity (273.2 mg/g) than N/EXK (231 mg/g) and U/EXK (178.4 mg/g). Beside the remarkable differences in textural properties, the advanced mathematical modeling and the corresponding steric and energetic parameters illustrate the mentioned uptake properties. The interface of C/EXK is highly saturated by active uptake sites (Nm = 158.8 mg/g) as compared to N/EXK (109.3 mg/g) and U/EXK (93.4 mg/g), which is in agreement with the characterization findings and the expected higher exposure of siloxane groups. Each of these sites can be filled with four dye molecules using C/EXK and N/EXK, which implies the vertical orientation of these adsorbed ions and the effective operation of multi-molecular mechanisms. The energetic (ΔE < 40 kJ/mol) and thermodynamic investigations indicate the spontaneous, physical, and exothermic uptake of safranin molecules by EXK particulates. These mechanisms might involve dipole bonding (2 to 29 kJ/mol), electrostatic attraction (2-50 kJ/mol), van der Waals forces (4 to 10 kJ/mol), and hydrogen bonding (<30 kJ/mol)